2019
DOI: 10.1155/2019/7490640
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Stock Brokers’ Trading Patterns: A Network Decomposition and Spatial Econometrics Approach

Abstract: Using a unique data set with all the daily transactions from the Santiago Stock Exchange, we develop a novel methodology that combines a network decomposition with a spatial econometrics technique to study how brokers’ characteristics and trading decisions may affect the stock market return. We present suggestive evidence of a mechanism by which structural changes of the transaction network between brokers affect the aggregate returns of the stock market. We find that brokers tend to trade with counterparties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
1
0
1
Order By: Relevance
“…Moreover, online trading had led to the expansion and extension of the capital market. Eberhard et al (2019) analyzed the trading patterns of stockbrokers, by collecting data of stockbrokers' everyday transactions from 2006 to 2015 at the Santiago stock exchange keeping the identification of stockbrokers anonymous and analyzing the same with the spatial econometrics technique. The study revealed that when the rate of return increased dramatically, stockbrokers preferred to make deals with those parties who had different volumes of sales within a day.…”
Section: Stockbrokers' Transactional Servicesmentioning
confidence: 99%
“…Moreover, online trading had led to the expansion and extension of the capital market. Eberhard et al (2019) analyzed the trading patterns of stockbrokers, by collecting data of stockbrokers' everyday transactions from 2006 to 2015 at the Santiago stock exchange keeping the identification of stockbrokers anonymous and analyzing the same with the spatial econometrics technique. The study revealed that when the rate of return increased dramatically, stockbrokers preferred to make deals with those parties who had different volumes of sales within a day.…”
Section: Stockbrokers' Transactional Servicesmentioning
confidence: 99%
“…Hasil penelitian (Mihaylov, Cheong, & Zurbruegg, 2015) menunjukkan bahwa ada beberapa bukti yang menunjukkan bahwa perkiraan pendapatan agregat oleh analis sekuritas berisi informasi yang berharga untuk prediksi harga emas di masa depan. Analis efek (broker) memiliki peran penting dalam pengembalian pasar misalnya dapat membantu meningkatkan efesiensi dengan mengurangi kemungkinan penggelembungan asset (Eberhard, Lavin, Montecinos-Pearce, & Arenas, 2019). Hasil penelitian (Yuan, Wu, & Xu, 2011) di Cina menunjukkan bahwa analis sekuritas Cina dapat menggunakan sarana pengumpulan informasi dan kemampuan analisis pakar untuk mengumumkan informasi perkiraan laba yang berharga, yang akan mendorong lebih banyak informasi spesifik perusahaan ke dalam harga saham.…”
Section: Metode Penelitianunclassified